2023
DOI: 10.3390/ph16010080
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-HBED-CC-WL-12 PET in Diagnosing and Differentiating Pancreatic Cancers in Murine Models

Abstract: Positron emission tomography (PET) has been proven as an important technology to detect the expression of programmed death ligand 1 (PD-L1) non-invasively and in real time. As a PD-L1 inhibitor, small peptide WL12 has shown great potential in serving as a targeting molecule to guide PD-L1 blockade therapy in clinic. In this study, WL12 was modified with HBED-CC to label 68Ga in a modified procedure, and the biologic properties were evaluated in vitro and in vivo. 68Ga-HBED-CC-WL12 showed good stability in sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Routine automated 68 Ga labeling was done as described above, and a log D 7.4 of −1.66 ± 0.08 ( n = 8) for 68 Ga-DOTA-WL12 was determined by shake-flask. Dynamic PET imaging in MDA-MB-231 xenografts revealed that similar to radiometalated WL12 conjugates comprising DOTAGA, , NOTA, HBED, or the respective radiofluorinated derivatives, 68 Ga-DOTA-WL12 showed a high and persistent uptake in the liver and a slow and incomplete blood clearance within the monitored time period of 90 min (Figure a). In contrast, 68 Ga-TRAP-WL12 was cleared much more rapidly from the blood and liver (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine automated 68 Ga labeling was done as described above, and a log D 7.4 of −1.66 ± 0.08 ( n = 8) for 68 Ga-DOTA-WL12 was determined by shake-flask. Dynamic PET imaging in MDA-MB-231 xenografts revealed that similar to radiometalated WL12 conjugates comprising DOTAGA, , NOTA, HBED, or the respective radiofluorinated derivatives, 68 Ga-DOTA-WL12 showed a high and persistent uptake in the liver and a slow and incomplete blood clearance within the monitored time period of 90 min (Figure a). In contrast, 68 Ga-TRAP-WL12 was cleared much more rapidly from the blood and liver (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…A cyclic peptide referred to as WL12 was one of the first reported nonprotein ligands for PD-L1 . In line with established strategies of radiotracer development, this peptide has been functionalized with various moieties comprising positron-emitting radionuclides ( 18 F, 64 Cu, 68 Ga) on the terminal amine of an ornithine side chain. These labels did not compromise its PD-L1 activity, suggesting that radiolabeled WL12 congeners indeed hold great promise as radiopharmaceuticals for in vivo mapping of PD-L1. However, the hitherto reported WL12-based positron emission tomography (PET) tracers showed an unsatisfactory performance in preclinical imaging experiments using tumor-xenografted mice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 68 Ga]Ga-NOTA-WL-12 uptake in the liver increased substantially and shifted toward the small intestines after adding WL-12 blocking ( 195 ). The group continues exploring ways to optimize the biological properties of this peptide-derived radiotracer further by testing other chelators, such as HBED-CC ( 196 ). Besides the initial study performed by Chatterjee et al ( 189 ), no further studies to elucidate structural features of the peptide have been conducted yet.…”
Section: Peptidesmentioning
confidence: 99%
“…Nuclear medicine molecular imaging, especially positron emission tomography (PET), showed significant benefits for the quantification of proteins and biochemical processes in vivo , including its high sensitivity, whole-body imaging, and noninvasiveness. , Currently, many PD-L1 PET imaging tracers based on antibodies, nanobodies, and peptides have been studied with promising applications in preclinical investigations, which demonstrated the power of PET imaging for the noninvasive quantification of PD-L1 expression. For example, 18 F-BMS986192, , 89 Zr-atezolizumab, , 68 Ga-W12, , and so many other radiotracers showed good clinical responses of immunotherapy in tumor patients correlated with PET imaging, even better than with immunohistochemistry for some tracers . However, there are still big challenges, including long metabolic half-life, instability, and high cost, for using these tracers.…”
Section: Introductionmentioning
confidence: 99%